Efficiency enhancement of silicon solar cells covered by GeO2-PbO glasses doped with Eu3+ and TiO2 nanoparticles - Gunji, R. M. [UNESP]; Mattos, G. R.S. [UNESP]; Bordon, C. D.S.; Gómez-Malagón, L. A.; Kassab, L. R.P. [UNESP] (Elsevier, 2020)
An objective of the solar industry is to improve the efficiency of the light -electricity conversion process of photovoltaic solar cells. An alternative to achieve this purpose is to manage the solar spectrum that is absorbed by the solar cell in order to match it with the solar cell responsivity. It can be done, for example through the downconversion process, covering the solar cell with photonic materials that can convert photons of the UV region to photons with energy close to the band gap energy of the solar cell. This process can be observed, for example, through the UV excitation of transparent glasses with low phonon energy hosting luminescent ions with energy levels in the VIS region. The luminescence from these energetic levels can be improved siting the luminescent ions in places with low symmetry. In the present study the optical response to the solar spectrum of GeO2-PbO glasses containing Eu3+ ions and titanium dioxide nanoparticles was explored to enhance the efficiency of polycrystalline silicon solar cells. Results revealed a maximum efficiency enhancement of 15.92% for the silicon solar cell covered with GeO2-PbO glass doped with 1% of Eu2O3 and 0.5% of TiO2 heat treated for 24 h. This efficiency enhancement was attributed to the location of the Eu3+ ions in sites of low symmetry of TiO2 nanoparticles.
Keywords: Down-conversion; Europium; Luminescent glasses; Photovoltaic cells; TiO2 nanoparticles